Spear and stockwhip : a tale of the Territory - Graves, Richard, 1898-1971. (Sydney : Dymock's Book Arcade, 1950)
"Ã¢ÂÂSpear and StockwhipÃ¢ÂÂ is the story of five boys who engage as drovers with Ã¢ÂÂChikkerÃ¢ÂÂ Jackson. The location of the story extends from North Queensland, across the Barkly Tablelands, and on to the Roper River in the Northern Territory. The adventures of the boys, with their lively interest in the wild open country, their encounters with nomad tribes, the taming of a wild aboriginal boy (who later becomes one of their droving team), their outwitting of a gang of cattle thieves, and finally their return to Sleepy Hollow, and unexpected fame and fortune make this a tale that no boy, young or old, will willingly put down until her has read the last line." -- Dust jacket.
Keywords: Occupations - Pastoral industry workers; Queensland (Qld); Northern Territory (NT)